UPAYA PENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VI DI SD NEGERI HILIR SPER MENGGUNAKAN METODE KOOPERATIF TIPE TUTOR SEBAYA PADA MATA PELAJARAN MATEMATIKA MATERI PENYAJIAN DATA - Rusidah, Rusidah (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2023)
Learning Mathematics students are expected to understand the concept of Mathematics correctly as it happens in everyday life. It means teaching that emphasizes cognitive, effective and psychomotor aspects of a person (students), educational emphasis leads to three aspects of education namely knowledge, skills and attitudes, which occur in the teaching and learning process systematically. Initial observations obtained by researchers showed that the implementation of Mathematics learning in Class VI of SDN Hilir Sper was not optimal. The approaches and media used by teachers are less varied. This causes mathematics to be difficult for students to understand and makes students less active. The problem in this study is whether using the cooperative peer tutor type method can improve the learning outcomes of students in Class VI SDN Hilir Sper in the subject of Mathematics in presenting data? The purpose of this research is to improve the learning outcomes of students in Class VI SDN Hilir Sper. This type of research is classroom action research with the research subjects being Class VI students consisting of 14 female students and 11 male students as well as Class VI teachers at SDN Hilir Sper. This research was conducted in 2 cycles, each cycle consisting of 1 meeting. Each cycle consists of four stages, namely planning, implementation, observation and reflection. Data collection techniques using tests and observations. The results of this study indicate an increase in the value of learning outcomes obtained by data on pre-cycle the average value achieved by students is 54.80 with a mastery percentage of 40%. In cycle I the average score achieved by students became 61.60 with a mastery learning of 56%. While in cycle II the average value of students rose to 72.00 with 100% mastery. Thus it can be concluded that the cooperative method of peer tutoring in Mathematics learning can improve learning outcomes for Class VI students at SDN Hilir Sper. The peer tutor type cooperative approach improves the quality of learning so it is suggested that it can be applied to other lessons